Suburban Islam: By Justine Howe (New York: Oxford University Press, 2018. 280 pages.) (American Journal of Islam and Society, 2019)
Justine Howe provides a rich ethnographic account of the Mohammed Alexander Russell Webb Foundation in the western Chicago suburbs from 2010 to 2014. Howe argues that the Webb Foundation functions as a third space, an in-between space that critiques local masjids and “engenders possibilities for new ways of being” (9). The organization was founded by and specifically targets university educated, culturally American, “unmosqued” Muslims who feel like outsiders to mainstream American culture and Chicago masjids that have increasingly become influenced by Salafis. Their religion (and often race) marks Webb members as not fully American and local masjids privilege cultural Islam over “true” Islam, forcing them to exist on the margins.